Tetrakis(μ-acetato-κ(2) O:O′)-bis[(3-pyridinecarboxaldehyde-κN′)]dicopper(II)(Cu—Cu) - Cruz-Enriquez, Adriana (International Union of Crystallography, 2012)
The binuclear title compound, [Cu(2)(CH(3)CO(2))(4)(C(6)H(5)NO)], is located about a center of inversion. The Cu(II) atoms are connected [Cu—Cu = 2.6134 (5) Å] and bridged by four acetate ligands. Their distorted octahedral coordination geometry is completed by a terminal pyridine N atom of a 3-pyridincarboxaldehyde ligand. In the crystal, the complex molecules are linked by C—H⋯O hydrogen bonds, forming two-dimensional networks lying parallel to the ab plane. These networks are linked via C—H⋯O hydrogen bonds involving inversion-related 3-pyridinecarboxaldehyde ligands, forming a three dimensional supramolecular architecture.